Production technology of complex fertilizers based on dispersed activated sludge - Бєлянська, Олександра Ростиславівна; Іванченко, Анна Володимирівна; Волошин, Микола Дмитрович (Eastern-European Journal of Enterprise Technologies, 2015)
Nowadays there is a Ukraine’s resource dependence on external sources of nitrogen-phosphorus-potassium raw material for fertilizers production, so there is the need to create a technology for using these substances from waste. The source of nitrogen, phosphorus and potassium formation is the excess activated sludge that is accumulated for years in the wastewater treatment plant territory and overfills sludge drying beds. However, the activated sludge contains up to 99.8% of moisture, which prevents its widespread use in the fertilizers production technology. One way to reduce the moisture content in the sludge is its pre-machining, namely dispersion. It was proved in the paper that during machining with the disperser on the disperser rotor speed 17s-1 (Re=42,4•103) there is the partial destruction of the activated sludge microorganism cells, sludge structure becomes denser. It was found that when using dispersion processes, sludge swelling in the further settling is delayed by 40 minutes. A technological production scheme of complex fertilizers, which first uses dispersion process that accelerates activated sludge settling (sludge residual volume is decreased by 50%, and the humidity is reduced from 99.8 to 92%) was developed. The research has allowed to expand the raw material base to produce complex fertilizers on the example of Dniprodzerzhynsk city due to using the activated sludge, sludge of calcium nitrate production and create a technology with a complex fertilizer output of 932.75 tons/year (68%) of dry matter.